2023
DOI: 10.1038/s41467-023-36868-4
|View full text |Cite
|
Sign up to set email alerts
|

Key innovations and the diversification of Hymenoptera

Abstract: The order Hymenoptera (wasps, ants, sawflies, and bees) represents one of the most diverse animal lineages, but whether specific key innovations have contributed to its diversification is still unknown. We assembled the largest time-calibrated phylogeny of Hymenoptera to date and investigated the origin and possible correlation of particular morphological and behavioral innovations with diversification in the order: the wasp waist of Apocrita; the stinger of Aculeata; parasitoidism, a specialized form of carni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 127 publications
5
45
2
Order By: Relevance
“…, an entomofauna essentially modern morphology (van Eldijk et al , 2017). In Argentina, extant orders such as Diptera ( trihennigma zavattierii Lara & Lukashevich, 2013), Hymenoptera ( Potrerilloxyela menendezi Lara et al , 2014), and true heteropterans have been recorded, illustrating that the evolution that led to nowadays ecosystems initiated during the Triassic and probably much older according to molecular dating (Lara et al , 2017, 2021; Blaimer et al , 2023; Nel pers. comm.…”
Section: Discussionmentioning
confidence: 99%
“…, an entomofauna essentially modern morphology (van Eldijk et al , 2017). In Argentina, extant orders such as Diptera ( trihennigma zavattierii Lara & Lukashevich, 2013), Hymenoptera ( Potrerilloxyela menendezi Lara et al , 2014), and true heteropterans have been recorded, illustrating that the evolution that led to nowadays ecosystems initiated during the Triassic and probably much older according to molecular dating (Lara et al , 2017, 2021; Blaimer et al , 2023; Nel pers. comm.…”
Section: Discussionmentioning
confidence: 99%
“…str. ), a relationship first hinted at in Hymenoptera‐wide analyses (Peters et al, 2017; see also Blaimer et al, 2023) and indicating that herbivorous cynipids do not form a monophyletic clade. Finally, the analysis suggested that the Eschatocerini may be the sister group of the Figitidae, although the evidence for this was weak and alternative placements appeared under some analysis settings.…”
Section: Introductionmentioning
confidence: 86%
“…It has generally been assumed that the phytophagous forms constitute a monophyletic lineage, the family Cynipidae, although it has been surprisingly difficult to find morphological characters supporting their monophyly (Liljeblad & Ronquist, 1998;Ronquist, 1999;Ronquist et al, 2015). The Cynipidae are deeply nested within the insect-parasitic Apocrita (Blaimer et al, 2023;Heraty et al, 2011;Klopfstein et al, 2013;Peters et al, 2017;Ronquist, 1995Ronquist, , 1999Sharkey et al, 2011), and all other members of the superfamily Cynipoidea are insect parasitoids, so it has long been clear that the phytophagous gall inducers and inquilines must have evolved from insect-parasitic ancestors. Except for the Cynipidae, the superfamily Cynipoidea comprises the families Austrocynipidae, Ibaliidae, Liopteridae and Figitidae (Ronquist, 1995(Ronquist, , 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in this review, the Hymenoptera provide unique features for this endeavour. They represent a highly diverse insect order (Forbes et al ., 2018; Blaimer et al ., 2023), encompassing a wide range of evolutionary radiations, including phytophagous sawflies, parasitoid wasps, and carnivorous as well as palynivore (bee) species (Fig. 2A).…”
Section: Introductionmentioning
confidence: 99%